Enhancing Islamic Education Quality: A Case Study of Principal's Leadership Management in Elementary Schools - Yanti Humaira Fitriyani; Maman Suherman (CV. Media Digital Publikasi Indonesia, 2026)
This study is predicated on the strategic role of principal leadership in enhancing the quality of Islamic Religious Education (PAI) in elementary schools, a domain still confronting multifaceted challenges. This research aimed to describe and analyze the principal's leadership management in improving the quality of PAI learning at SDN Ciawi and SDN 4 Pakemitan, Tasikmalaya Regency. The research employed a qualitative approach with a case study design. Data were collected through a triangulation of methods, including observation, in-depth interviews, and documentation studies, to ensure data validity and richness. The findings reveal that principals in both schools implement transformational and participatory leadership styles. Key strategies include active involvement in collaborative planning, continuous professional development for teachers, strengthening the school's religious culture through habituation programs, and fostering effective collaboration with teachers and parents. These interventions resulted in a significant increase in student learning motivation, the quality of instructional delivery, and overall academic and character-based learning outcomes in PAI. The study concludes that effective and visionary leadership management by the school principal is a critical determinant that substantially contributes to the enhancement of PAI learning quality at the elementary school level.